If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + 1) + -5 = 4(x + -3) Reorder the terms: 3(1 + 2x) + -5 = 4(x + -3) (1 * 3 + 2x * 3) + -5 = 4(x + -3) (3 + 6x) + -5 = 4(x + -3) Reorder the terms: 3 + -5 + 6x = 4(x + -3) Combine like terms: 3 + -5 = -2 -2 + 6x = 4(x + -3) Reorder the terms: -2 + 6x = 4(-3 + x) -2 + 6x = (-3 * 4 + x * 4) -2 + 6x = (-12 + 4x) Solving -2 + 6x = -12 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -2 + 6x + -4x = -12 + 4x + -4x Combine like terms: 6x + -4x = 2x -2 + 2x = -12 + 4x + -4x Combine like terms: 4x + -4x = 0 -2 + 2x = -12 + 0 -2 + 2x = -12 Add '2' to each side of the equation. -2 + 2 + 2x = -12 + 2 Combine like terms: -2 + 2 = 0 0 + 2x = -12 + 2 2x = -12 + 2 Combine like terms: -12 + 2 = -10 2x = -10 Divide each side by '2'. x = -5 Simplifying x = -5
| 2t-2y= | | y=x^3+7x^2-245x+35 | | 18=-1.8 | | -52-3=3x+20 | | 2x+15=63-5x | | 6x+5-3x=18+4x | | 1.2=2.5-3b | | 16x^2+16x-1=0 | | 4x^2+6=13 | | C-6=-22 | | x(x+10)+25=0 | | -4(x-5)=12(x+3) | | 6(2x-1)=-11(x+1) | | -2y+3x=2 | | 12x-2y=8 | | 4x+4x=8 | | -9r+5=-28 | | 0.4(y+3)=0.5(y-4) | | 5m+(2m+1)=23 | | 0+50*1-60-60*0+10=10 | | 2+4x=26-x | | 9(m+1)=6m | | 3.49x=78 | | 6x-14=-2x+26 | | x-4=3x-8 | | 3.49+x=78 | | y-2x=6 | | 2x-(4x-12)=3+x | | A+6=22 | | -11*-9= | | 10+1s=30 | | 3+3(2t-3)-3(4t+3)-7= |